Quercetin-Conjugated Superparamagnetic Iron Oxide Nanoparticles Protect AlCl3-Induced Neurotoxicity in a Rat Model of Alzheimer’s Disease via Antioxidant Genes, APP Gene, and miRNA-101 - Amanzadeh Jajin, Elnaz; Esmaeili, Abolghasem; Rahgozar, Soheila; Noorbakhshnia, Maryam (Frontiers in Neuroscience, 2021)
Alzheimer’s Disease (AD) is a neurodegenerative disease with cognitive impairment. Oxidative stress in neurons is considered as a reason for development of AD. Antioxidant agents such as quercetin slow down AD progression but the usage of this flavonoid has limitations because of its low bioavailability. We hypothesized that quercetin-conjugated superparamagnetic iron oxide nanoparticles (QT-SPION) have a better neuroprotective effect on AD than free quercetin and regulates the antioxidant, apoptotic, and APP gene, and miRNA-101. In this study, male Wistar rats were subjected to AlCl3, AlCl3+QT, AlCl3+SPION, and AlCl3+QT-SPION for 42 consecutive days. Behavioral tests and qPCR were used to evaluate the efficiency of treatments. Results of behavioral tests revealed that the intensity of cognitive impairment was decelerated at both the middle and end of the treatment period. The effect of QT-SPIONs on learning and memory deficits were closely similar to the control group. The increase in expression levels of APP gene and decrease in mir101 led to development of AD symptoms in rats treated with AlCl3 while these results were reversed in the AlCl3+QT-SPIONs group. This group showed similar results with the control group. QT-SPION also decreased the expression levels of antioxidant enzymes along with increases in expression levels of anti-apoptotic genes. Accordingly, the antioxidant effect of QT-SPION inhibited progression of cognitive impairment via sustaining the balance of antioxidant enzymes in hippocampus of AD model rats.